Scapegoats of the justice system: problematizing necropolitics and state violence of Black disability in select American films - Abhishika Dawn; G. Alan (Humanities & Social Sciences Communications)
Abstract Understanding the politics of race in relation to a social marker like disability can provide a more nuanced perspective to understand the lived experiences of individuals within intersecting oppressive structures. While progress has been made in recognising the rights and privileges of black disabled people, the socio-political landscape has been layered with exclusions, and the deployment of necropolitics by the white, able-bodied individuals reduces them to bare life (zoē) and, in extreme cases, results in their death. The films The Green Mile and Just Mercy expound on the ostracization of John Coffey and Herbert Richardson, who are members of specific ethnic groups and are disabled. These characters face systematic oppression primarily due to their race, which, combined with their disability, renders them expendable and hinders their ability to thrive. Informed by the social model of disability and Achille Mbembe’s Necropolitics, this paper argues that the black disabled characters are highly vulnerable to state-inflicted violence that sometimes culminates in their demise.